2016
DOI: 10.1093/humrep/dew018
|View full text |Cite
|
Sign up to set email alerts
|

Corroborating evidence for platelet-induced epithelial-mesenchymal transition and fibroblast-to-myofibroblast transdifferentiation in the development of adenomyosis

Abstract: Support for data collection and analysis was provided by grants from the National Science Foundation of China. None of the authors has anything to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
113
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 85 publications
13
113
1
Order By: Relevance
“…However, as DNA damage, oxidative stress, hypoxia, and oncogene (such as KRAS and YAP) activation induce cellular senescence and senescence would curtail fibrosis, it is likely that in older and thus more fibrotic lesions may experience less hypoxia and less oxidative stress (due to increased fibrotic content and thus reduced cellularity, less hemorrhage and thus iron overload) and less DNA damage (as seen by reduced γ‐H2AX expression ), the pressure for cellular senescence may be reduced, especially in the stromal compartment. This would be consistent with reduced Caveolin‐1 expression in adenomyosis, which can be highly fibrotic, especially as lesions get older . This also would be consistent with seemingly progressive decrease in CCN1 expression in older lesions .…”
Section: Changing Pressure For Genomic Alteration Due To Oxidative Stsupporting
confidence: 72%
See 1 more Smart Citation
“…However, as DNA damage, oxidative stress, hypoxia, and oncogene (such as KRAS and YAP) activation induce cellular senescence and senescence would curtail fibrosis, it is likely that in older and thus more fibrotic lesions may experience less hypoxia and less oxidative stress (due to increased fibrotic content and thus reduced cellularity, less hemorrhage and thus iron overload) and less DNA damage (as seen by reduced γ‐H2AX expression ), the pressure for cellular senescence may be reduced, especially in the stromal compartment. This would be consistent with reduced Caveolin‐1 expression in adenomyosis, which can be highly fibrotic, especially as lesions get older . This also would be consistent with seemingly progressive decrease in CCN1 expression in older lesions .…”
Section: Changing Pressure For Genomic Alteration Due To Oxidative Stsupporting
confidence: 72%
“…Both animal and human data lend support for the notion that endometriotic lesions are fundamentally wounds undergoing repeated tissue injury and repair (ReTIAR) . Similar processes also occur in adenomyosis, due to the shared commonality of cyclic bleeding …”
Section: A Primer On the Natural History Of Endometriosismentioning
confidence: 82%
“…Fibrosis is now recognized as a prominent feature of endometriosis 8, 21 as well as of adenomyosis 51, 52 . Remarkably, EZH2 is intimately involved in fibrogenesis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…[6] Fundamental analysis studies in recent years demonstrated that CA125, PLT, and NEU may related to the development and progression of the inflammatory pathology of endometriosis via the inflammation-associated molecular mechanism. [14,15] It was reported that patients with preoperative CA125 levels higher than 65 IU/mL were at high risk for advanced-stage or severe pelvic adhesion. [16] Numerous studies demonstrated that both PLT and NEU were implicated in the pathogenesis of endometriosis and adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…[20] The significant correlations between PLT and NLR and PDA in this study suggest that both of PLT and NLR may be related to the inflammatory pathogenesis of adenomyosis. [14,18] …”
Section: Discussionmentioning
confidence: 99%